The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.worlddev.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The short-term impacts of development-induced displacement on wealth and subjective well-being in the Brazilian Amazon

Abstract: Summary Displacement due to development projects such as dams, mines, and urban infrastructure often leads to livelihood decline among affected communities. The challenge, therefore, lies in implementing projects that achieve national or regional development goals while also generating positive social and economic outcomes for displaced populations. This paper uses a longitudinal, mixed-methods design to understand the short-term changes in wealth and subjective well-being of households displaced due to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 44 publications
(55 reference statements)
2
42
0
12
Order By: Relevance
“…Negative case studies predominate, but a few papers report positive social impacts, and when they do, they mostly focus on infrastructural aspects such as increased electricity production and improved flood control (Kirchherr, Pohlner, & Charles, ). A few case studies report positive social impacts of dams on resettlers and displaced communities (e.g., Randell, ; Wilmsen, ) or at least reduced negative impacts (e.g., Burrier, ). These are brought about by significant investments in compensation schemes and regional economic development by dam builders and national governments, the kinds of initiatives recommended by the WCD.…”
Section: The Persistent Impacts Of Large Dams In a Post‐wcd Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative case studies predominate, but a few papers report positive social impacts, and when they do, they mostly focus on infrastructural aspects such as increased electricity production and improved flood control (Kirchherr, Pohlner, & Charles, ). A few case studies report positive social impacts of dams on resettlers and displaced communities (e.g., Randell, ; Wilmsen, ) or at least reduced negative impacts (e.g., Burrier, ). These are brought about by significant investments in compensation schemes and regional economic development by dam builders and national governments, the kinds of initiatives recommended by the WCD.…”
Section: The Persistent Impacts Of Large Dams In a Post‐wcd Worldmentioning
confidence: 99%
“…Such changes are also arguably a consequence of heightened global awareness of environmental and social issues in a post‐WCD world, even if it is evidently not possible to attribute this heightened awareness directly to the WCD's work. Researchers continue to stress the need for long‐term studies to confirm whether such positive impacts are sustainable or only temporary (Randell, ; Scudder, ; Wilmsen, ).…”
Section: The Persistent Impacts Of Large Dams In a Post‐wcd Worldmentioning
confidence: 99%
“…Despite the findings that monetary compensation alone is not sufficient to prevent impoverishment after displacement (Cernea ; Downing ; Fernandes Serra ), Randell () discovered that in the case of Belo Monte, monetary compensation enabled the majority of households to maintain or improve livelihoods in the first few years after migration. These findings suggest that if payments are large enough for households to replace lost property and assets at market value as well as invest in new assets, compensation may in fact enable households to improve their standards of living.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous DIDR studies and livelihood studies , Sayatham and Suhardiman, 2015, Souksavath and Nakayama, 2013, Scoones, 2009, Wilmsen et al, 2011a, Randell, 2016 have focused mainly on the short-term changes of resettlement and ignored the local dynamics relating to the livelihood reconstruction process. In this case, the research found longterm impoverishment of the resettled people because of the hydropower dam and agricultural development in the context of changing lifestyle of subsistence farmers and land tenure.…”
Section: Discussionmentioning
confidence: 99%